2002
DOI: 10.1006/viro.2002.1536
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Analysis of the DNA Polymerase Gene of Shrimp White Spot Syndrome Virus

Abstract: The white spot syndrome virus DNA polymerase (DNA pol) gene (WSSV dnapol) has already been tentatively identified based on the presence of highly conserved motifs, but it shows low overall homology with other DNA pols and is also much larger (2351 amino acid residues vs 913-1244 aa). In the present study we perform a transcriptional analysis of the WSSV dnapol gene using the total RNA isolated from WSSV-infected shrimp at different times after infection. Northern blot analysis with a WSSV dnapol-specific ribop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
69
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 62 publications
2
69
0
1
Order By: Relevance
“…It was recently erected as the type species of genus Whispovirus in the family Nimaviridae (56). Although the complete sequence of the WSSV genome has been known for several years (7,55,60), knowledge of the biological functions of the viral proteins is still quite poor. The WSSV immediate-early gene ie1 (31) was recently shown to use a shrimp signal transducer and activator of transcription (STAT) as a transcription factor to enhance its expression and contribute to its high promoter activity in host cells (30).…”
mentioning
confidence: 99%
“…It was recently erected as the type species of genus Whispovirus in the family Nimaviridae (56). Although the complete sequence of the WSSV genome has been known for several years (7,55,60), knowledge of the biological functions of the viral proteins is still quite poor. The WSSV immediate-early gene ie1 (31) was recently shown to use a shrimp signal transducer and activator of transcription (STAT) as a transcription factor to enhance its expression and contribute to its high promoter activity in host cells (30).…”
mentioning
confidence: 99%
“…To assist in identifying the root sources of WSSV infection in crayfish farmed in China and devising strategies to control its spread Despite associations between the pathogenicity and protein profiles of WSSV isolates examined from different hosts (Wang et al 1999, 2000, Waikhom et al 2006, the factors dictating virulence are likely to be complex. Genome sequence data on WSSV isolates from different penaeid shrimp species, as well as the blue crab Callinectes sapidus, suggest they have a common recent ancestry (Chang et al 2001, Chen et al 2002, Moon et al 2003, Dieu et al 2004. As the hr9 sequence determined for the 4 Procambarus clarkii isolates was identical to reference WSSV-TW/WSSV-TH isolates (Wang et al 2000, van Hulten & Valk 2001 and as their transposase sequence was identical to reference WSSV-TH/WSSV-CN isolates (van Hulten & Valk 2001, Yang et al 2001, all these isolates also appear to have a common recent ancestry.…”
Section: Discussionmentioning
confidence: 93%
“…However, the complete sequence of WSSV has recently been reported by Van-Hulten et al (2002). Marks et al (2003) reported that a VP-15 was the only major protein structure gene with a consensus TATA-box compared to VP-19, VP-24, and VP-28, in which the earlier onset of transcription of VP-15 could be regulated by this TATA-box, as in other WSSV genes which have been shown or are likely to be expressed early in an infection (Tsai et al, 2000;Liu et al, 2001;Chen et al, 2002). Van-Hulten et al (2002) stated that VP-15 is a very basic protein and resembles histone protein which functions as a DNA-binding protein in the WSSV nucleocapsid.…”
Section: Transcription Factor and Amino Acid Deduction Of Vp-15 Wssvmentioning
confidence: 99%